THz and IR spectroscopy of endofullerene H2O@C60. Issue 1 (July 2021) - Melentev, Alexander; Zhukov, Sergey; Balos, Vasileios; Hoffman, Gabriela; Alom, Shamim; Belyanchikov, Mikhail; Zhukova, Elena; Dressel, Martin; Bacanu, George; Abramov, Pavel; Levitt, Malcolm; Whitby, Richard; et al.
Abstract: Terahertz time-domain and infrared Fourier-transform spectroscopy techniques are used to investigate the properties of H2 O@C60 endofullerene in 6 K – 300 K temperature interval. A number of absorption lines associated with rotational transitions of water molecule entrapped inside C60 cages are observed and assigned. Fitting the resonances with Lorenzian lineshapes allowed us to obtain temperature dependencies of absorption lines parameters – frequency, strength and damping.